1963
DOI: 10.1063/1.1733492
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and Disproportionation Reactions of Monochloroethyl and Trichloromethyl Radicals

Abstract: The recombination and disproportionation reactions of CH2CH2Cl and CCl3 radicals have been investigated. Trichloromethyl radicals and monochloroethyl radicals were produced by photolyzing carbon tetrachloride in the presence of ethylene. The main features of the resulting reaction mechanism are given by reactions (1) to (8) CCl4+hν→CCl3+Cl,Cl+C2H4→C2H4Cl,2C2H4Cl→(C2H4Cl)2,2C2H4Cl→C2H4+C2H4Cl2,2C2H4Cl→C2H5Cl+C2H3Cl,2CCl3→C2Cl6,C2H4Cl+CCl3→CCl3C2H4Cl,C2H4Cl+CCl3→CHCl3+C2H3Cl.The following rate constants have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

1964
1964
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…Only measurements for the disproportionation−recombination ratios ( k d / k c ) for C 2 H 4 Cl radicals are known. They have been studied between 3 and 760 Torr pressures by the reaction scheme: Rate constant ratios for reactions 12a and 12c are reported as 0.05, 0.1, 0.21, and 0.36, whereas the ratios for reactions 12b and 12c are 0.1, 0.21, and 0.09 . Concerning the disproportionation variant 12b, we could find neither traces of dichloroethane in the mass range 98−100, nor any measurable increase of mass 28 signal intensity over that from the C 2 H 5 Cl fragmentation.…”
Section: Discussionmentioning
confidence: 94%
“…Only measurements for the disproportionation−recombination ratios ( k d / k c ) for C 2 H 4 Cl radicals are known. They have been studied between 3 and 760 Torr pressures by the reaction scheme: Rate constant ratios for reactions 12a and 12c are reported as 0.05, 0.1, 0.21, and 0.36, whereas the ratios for reactions 12b and 12c are 0.1, 0.21, and 0.09 . Concerning the disproportionation variant 12b, we could find neither traces of dichloroethane in the mass range 98−100, nor any measurable increase of mass 28 signal intensity over that from the C 2 H 5 Cl fragmentation.…”
Section: Discussionmentioning
confidence: 94%
“…Wijnen et al also used ultraviolet SC,H,Cl -.+ CH,ClCH,CH,CH,Cl ( 5 ) C1 transfer C,H,Cl t C,H4C1-C,H, t C,H,Cl, (6) H transfer C,H,Cl + C,H,Cl-C,H,Cl + C,H,Cl ( 7 1 photolysis of C C 4 as a C1-atom source for reaction with ethylene. 6 In these experiments, disproportionation products from C1 and H transfer between C2H4C1 radicals were observed, as in (6) and (7). The yields of the observed two-carbon products (C2H3C1, C2H5C1, CzH4C12) indicated that the disproportionation processes 6 and 7 were 50.1 as probable as combination 5 .…”
Section: (1)mentioning
confidence: 99%
“…I1 semble donc que la formation du butadiPne doit &re attribuke surtout A la reaction [7], sans toutefois rejeter totalement une participation de la rCaction [S] E n admettant la rkaction [6] pour la formation d u chlorure de vinyle, on devrait trouver une dCpendance liniiaire de la concentration en CC14. E n fait, on trouve une dCpendance du carrk de la concentration (Fig.…”
Section: Formation D U Butadieneunclassified
“…Mais les rkactions [6] e t [9] sont compCtitives; on peut alors expliquer que la formation du chlorure de vinyle dCpende du c a r d de la concentration en iodure de vinyle. Dans le cas de l'CthylCne, la dkpendance de la concentration n'est pas aussi simple (Fig.…”
Section: Formation D U Butadieneunclassified
See 1 more Smart Citation